2010
DOI: 10.1097/fbp.0b013e32833fa7df
|View full text |Cite
|
Sign up to set email alerts
|

Current pharmacological models of social withdrawal in rats

Abstract: Social dysfunction in schizophrenia is one of the core negative symptoms, which to date is not adequately addressed by treatment with both typical and atypical antipsychotics. A number of different pharmacological models of social withdrawal are used to mimic social dysfunction in rats, such as amphetamine, N-methyl-D-aspartic acid antagonists, cannabinergic and serotonergic receptor ligands. The purpose of this review is to discuss and compare these models of social withdrawal with a focus on their face, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 177 publications
(246 reference statements)
1
26
0
Order By: Relevance
“…Also, PCP-treated rats represent the best pharmacological model of social withdrawal (negative symptom) in term of construct, face, and predictive validity (Gururajan et al, 2010). We previously showed that systemic administration of URB597, a drug that increases AEA levels by blocking its catabolic enzyme fattyacid amide hydrolase (FAAH), reverses PCP-induced social withdrawal (Seillier et al, 2010), thus strengthening the idea that cannabinoid compounds could attenuate negative symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…Also, PCP-treated rats represent the best pharmacological model of social withdrawal (negative symptom) in term of construct, face, and predictive validity (Gururajan et al, 2010). We previously showed that systemic administration of URB597, a drug that increases AEA levels by blocking its catabolic enzyme fattyacid amide hydrolase (FAAH), reverses PCP-induced social withdrawal (Seillier et al, 2010), thus strengthening the idea that cannabinoid compounds could attenuate negative symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…These include hyperactivity, social withdrawal (Gururajan et al, 2010) and disrupted PPI (Geyer et al, 2001). Using this MK-801 rodent model of aspects of schizophrenia, we evaluated the antipsychotic potential of CBD.…”
Section: Speciesmentioning
confidence: 99%
“…Carefully validated animal models combined with appropriate tests for negative symptoms in animals form a critical part of the development of new therapeutic strategies for negative symptoms (Barnes et al, 2014a;Neill et al, 2014). However, many aspects of negative symptom domains have been poorly investigated in animal studies and when they have, the most successful work has been conducted on the social withdrawal domain in rats (Gururajan et al, 2010;Moser, 2014;Neill et al, 2010Neill et al, , 2014Wilson and Koenig, 2014). These studies are certainly valuable and of ethological relevance in such a gregarious species.…”
Section: Introductionmentioning
confidence: 95%